Atta sexdens rubropilosa attractiveness to eucalyptus plants previously attacked or not by Thyrinteina arnobia - de Oliveira, Hamilton Gomes; Lacerda, Fabrícia Gonçalves; Marinho, Cidália Gabriela Santos; Della Lucia, Terezinha Maria Castro (Pesquisa Agropecuaria Brasileira, 2004)
The induced defense system of plants is activated after the occurrence of damage by a herbivore. The objective of this work was to evaluate whether plants of Eucalyptus grandis previously attacked by larvae of Thyrinteina arnobia become resistant to cutting by the leaf-cutting ant Atta sexdens rubropilosa. There was no significant difference in the lapse of time spent by the workers of this ant before they started cutting plants previously attacked or not. There was significant reduction in the size of leaf fragments cut by the ants. It was concluded that plants previously attacked were less attractive to the leaf cutter due to the activation of their induced defense system.